Impact of vehicle parking certificate scheme on freight operations - Ching, Yuet Hong. (2008)
This research is part of a survey conducted to better understand the operations of the freight transport industry. The objective of the study is to investigate how traffic management measures and information technology can facilitate freight transportation in Singapore. This dissertation focuses specially on the mechanism of the Vehicle Parking Certificate Scheme on heavy goods vehicles.